A Metal–Organic Framework Stabilizes an Occluded Photocatalyst. Issue 34 (11th July 2013) - Han, Shuangbing; Wei, Yanhu; Grzybowski, Bartosz A.
<x xml:space="preserve">Abstract</x> Occlusion and confinement of a [Ru(bpy)3]Cl2 photocatalyst in the cavities of a γ‐cyclodextrin (CD) metal–organic framework (MOF) does not affect the catalyst's activity but prevents its photodegradation. Additionally, the OH− ions and/or ROH groups present inside the CD‐MOF act as electron donors and complete the catalytic cycle. The occlusion approach is a technically straightforward alternative to the covalent modification of MOF scaffolds with catalytic units.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>